Bariatric surgery among patients with heart failure: a systematic review and meta-analysis. Issue 2 (8th December 2018) - Berger, Sebastian; Meyre, Pascal; Blum, Steffen; Aeschbacher, Stefanie; Ruegg, Marco; Briel, Matthias; Conen, David
Abstract : Background: Bariatric surgery reduces cardiovascular risk in obese patients. Heart failure (HF) is associated with an increased perioperative risk following bariatric surgery. This systematic review aimed to assemble the evidence on bariatric surgery in patients with known HF and the potential effect of bariatric surgery on incident HF in obese patients without prevalent HF. Methods: We performed a comprehensive literature search up to 30 September 2017 and included studies comparing bariatric surgery to non-surgical treatment in patients with known presurgical HF. To assess whether bariatric surgery has any effect on incident HF, we also assembled studies looking at new-onset HF among patients without HF prior to surgery. Results: We found five observational studies (0 randomised trials) comparing bariatric surgery with non-surgical treatment in patients with a diagnosis of HF prior to surgery. A review of the available studies (n=676 patients) suggested reduced admission rates for HF exacerbation and increased left ventricular ejection fraction after bariatric surgery. No meta-analysis was possible due to the heterogeneous nature of these studies. Seven studies (one randomised trial) reported data on new-onset HF in obese patients without HF prior to bariatric surgery (n=111 127 patients). When comparing surgical to non-surgical treatment groups, the pooled univariable and multivariable HRs for incident HF were 0.28 (95% CI 0.13 to 0.55) and 0.44 (95% CI 0.36 to 0.55), respectively. Conclusion: In this systematic review, no randomised trial assessed the benefits and risks of bariatric surgery in obese patients with concomitant HF. Available studies do, however, show that surgery might prevent incident HF.